High-temperature-resistant ultra-soft acrylic heat-conducting gasket and preparation method thereof

By combining a high thermal conductivity filler with a low Tg value acrylic monomer and prepolymer, the silicone volatile pollution of the silicone thermal conductivity gasket and the insufficient high temperature resistance and mechanical properties of the acrylic thermal conductivity gasket were solved, and a high thermal conductivity and low hardness acrylic thermal conductivity gasket was prepared, which was suitable for high temperature environments.

CN120535889AInactive Publication Date: 2025-08-26JIANGSU MINORU TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510820430.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-19
Publication Date
2025-08-26
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing silicone thermal conductivity gaskets have problems such as volatilization of silicone during long-term use, resulting in poor insulation of contaminated devices. The acrylic thermal conductivity gaskets have shortcomings in their high temperature resistance and mechanical properties, and it is difficult to meet the requirements of stable use at high temperatures.

Method used

Acrylic monomers and prepolymers with low glass transition temperature are used as colloids, combined with thermal fillers such as alumina, boron nitride, aluminum nitride, silicon carbide, and acrylic thermal gaskets are prepared by vacuum stirring, calendering and high-temperature baking. Acrylic plasticizers, antioxidants and coupling agents are added to improve flexibility and high-temperature resistance.

Benefits of technology

Acrylic thermal conductivity gasket with controllable thickness, excellent thermal conductivity and good mechanical strength was prepared. It has excellent high temperature resistance and low hardness, avoiding pollution problems caused by volatilization of silicones and is suitable for high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005456454880000111
    Figure BDA0005456454880000111
  • Figure BDA0005456454880000131
    Figure BDA0005456454880000131
  • Figure BDA0005456454880000151
    Figure BDA0005456454880000151
Patent Text Reader

Abstract

The invention relates to the technical field of thermal interface materials, and particularly discloses a high-temperature-resistant ultra-soft acrylic heat-conducting gasket and a preparation method thereof. Colloid comprises an acrylic monomer prepolymer, an acrylic plasticizer, a cross-linking agent, a coupling agent, a thermal initiator and an antioxidant; the selected monomer is an acrylic acid soft monomer with a low Tg value, and the acrylic acid monomer prepolymer is prepared in two modes of thermal polymerization and photopolymerization. And the heat-conducting filler part consists of one or more of aluminum oxide, boron nitride, aluminum nitride and silicon carbide. The colloid and the heat-conducting filler part are subjected to vacuum stirring and mixing, calendering by a calender and curing molding, and the acrylic acid heat-conducting gasket prepared by the method is controllable in thickness, excellent in heat-conducting property and good in mechanical strength and insulating property. The monomers selected by the prepolymer and the plasticizer of the colloid part are low-Tg acrylic acid soft monomers, and the formula does not involve volatile substances at high temperature, so that the gasket has excellent flexibility and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal interface materials, in particular to a high-temperature resistant ultra-soft acrylic thermally conductive pad and a preparation method thereof. Background Art

[0002] Thermal pads are commonly used to transfer heat from heat-generating components in electronic and electrical equipment to heat sinks, metal covers, and other heat-dissipating components. Common thermal pads are based on silicone, with certain metal oxides and various thermally conductive auxiliary materials added through a specialized process. Thermal pads are polymer composite thermally conductive materials that use silicone resin as a bonding material and are filled with thermally conductive powder to achieve thermal conductivity.

[0003] Currently, silicone thermal gaskets are commonly used on the market. Due to their high thermal conductivity, high temperature resistance, excellent physical properties, and low odor, they have long-term stability. However, during long-term use, due to the presence of some small molecules inside the gasket that have not been fully cross-linked, they will gradually release over time and overflow the surface of the gasket, which is often called silicone volatilization, and even oil leakage. The small molecules of silicone volatilization are easily adsorbed on the surface of the working device to which they are attached, contaminating the device and even causing the insulation at the contacts of the electronic components to deteriorate, affecting the normal switching of the circuit. In applications such as lens devices, such as cameras and displays, the silicone oil seeping from the silicone gasket will be adsorbed on the surface of the device and migrate, causing the lens device to be contaminated and blurred and unable to be used normally.

[0004] In response to a series of problems that arise during the use of silicone gaskets, the idea of ​​using silicone-free thermal gaskets as a replacement has emerged. Early on, some people proposed the idea of ​​using polyurethane thermal gaskets, but in fact, the thermal conductivity of thermal gaskets prepared with polyurethane rubber as the bonding part is far lower than that of silicone gaskets at the same ratio. In addition, polyurethane thermal gaskets have extremely poor weather resistance and cannot meet the requirements of use under most conditions. Subsequently, the idea of ​​acrylic thermal gaskets was proposed. Thermal gaskets prepared with acrylic rubber or specific monomers as the matrix have higher thermal conductivity, but weather resistance is still a major problem.

[0005] Since the high-temperature resistance of acrylic esters is far inferior to that of silicone and their mechanical properties are relatively poor, it has always been a difficult problem to use an acrylic system to prepare a thermally conductive gasket that is both resistant to high temperatures and maintains good mechanical properties. In order to improve the heat resistance and mechanical properties of the gasket, epoxy-modified acrylic resins or monomers with low glass transition temperatures are commonly used on the market as the colloidal part of the gasket. The use of high-viscosity epoxy resins can greatly improve the mechanical properties of the gasket, but oxidation reactions are prone to occur at high temperatures, causing double bonds to break, resulting in the gasket becoming hard and brittle. Monomers with low Tg values ​​can indeed solve the problem of gaskets not being resistant to high temperatures, but since the viscosity of the monomers themselves is relatively low, when preparing low-hardness thermally conductive gaskets, the viscosity of the mixture will be relatively low, making it difficult to produce and form, and thicker products cannot be prepared. Therefore, how to meet the high-temperature resistance performance conditions of the gasket and meet the production thickness and hardness requirements is a problem worthy of deep consideration. For this purpose, a high-temperature resistant ultra-soft acrylic thermally conductive gasket and a preparation method thereof are provided. Summary of the Invention

[0006] The purpose of the present invention is to provide a high-temperature resistant ultra-soft acrylic thermal conductive pad and a preparation method thereof in order to solve the problems raised by the above-mentioned background technology in view of the defects of the prior art.

[0007] To achieve the above objectives, the present invention provides the following technical solution: a high-temperature resistant ultra-soft acrylic thermally conductive gasket, comprising a colloid and a thermally conductive filler, wherein the colloid is composed of a mixture of one or more acrylic monomers with a low glass transition temperature and acrylic monomer prepolymers, and further contains a photoinitiator or thermal initiator capable of initiating polymerization of the monomers; the colloid accounts for 5 to 15% of the total weight of the thermally conductive gasket;

[0008] The heat-conducting filler is composed of one or more of aluminum oxide, boron nitride, aluminum nitride, and silicon carbide, and the heat-conducting filler accounts for 85-95% of the total weight of the heat-conducting gasket.

[0009] As a preferred technical solution of the present invention, the acrylic monomer is an acrylic monomer with a Tg value not greater than 0 and a carbon number not exceeding 20; the acrylic monomer also includes an acrylic monomer with a Tg value greater than 20 and an alkyl number not exceeding 20.

[0010] As a preferred technical solution of the present invention, the acrylic monomer prepolymer contained in the colloid is specifically any one or more of ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, and hexyl methacrylate, and its molecular weight is between 500-20,000.

[0011] As a preferred technical solution of the present invention, the thermal initiator or photoinitiator is an organic peroxide;

[0012] Organic peroxides include: one or more combinations of acyl peroxides, hydroperoxides, dialkyl peroxides, ester peroxides, ketone peroxides, and dicarbonate peroxides. The amount of the thermal initiator or photoinitiator added should be 1-5% of the mass of the acrylic monomer.

[0013] As a preferred technical solution of the present invention, the acyl peroxide is benzoyl peroxide or lauroyl peroxide; the hydroperoxide is cumene hydroperoxide or tert-butyl hydroperoxide; the dialkyl peroxide is di-tert-butyl peroxide or diisopropyl peroxide; the ester peroxide is tert-butyl perbenzoate or tert-butyl pervalerate; the ketone peroxide is methyl ethyl ketone peroxide or cyclohexanone peroxide; and the dicarbonate peroxide is diisopropyl peroxydicarbonate or dicyclohexyl peroxydicarbonate.

[0014] As a preferred technical solution of the present invention, the colloid further comprises an acrylic plasticizer, an antioxidant, a cross-linking agent, a flame retardant, and a coupling agent;

[0015] The acrylic plasticizer is a polymer formed by polymerization of acrylic acid monomers, specifically including any one or more combinations of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, and isobutyl acrylate, and the molecular weight of the plasticizer is controlled at 500-5000;

[0016] The antioxidant is a hindered phenol, including any one or more combinations of 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate) ester, and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate;

[0017] The coupling agent is a phthalate coupling agent, including any one or more combinations of monoalkoxy type, pyrophosphate type, chelate type and coordination type.

[0018] A method for preparing a high-temperature resistant ultra-soft acrylic thermally conductive gasket as described above, the specific preparation steps are as follows: a colloid and a thermally conductive filler are mixed and stirred and degassed to obtain a thermally conductive slurry, both sides of the thermally conductive slurry are placed between PET release films, pressed into a sheet by a calender, and then baked and cured at high temperature, and after curing, an acrylic thermally conductive gasket is obtained.

[0019] As a preferred technical solution of the present invention, the acrylic thermal conductive gasket has a thickness of 0.2mm-10mm, a thermal conductivity coefficient of 1.5-8W, and a hardness of ASK C 5-50; a substrate is added during the calendering process to obtain an acrylic thermal conductive gasket containing a substrate, or one side of the release film is replaced with a PET film to obtain an acrylic thermal conductive gasket with a non-sticky side.

[0020] Compared with the prior art, the present invention has the following beneficial effects: the colloid part of the present invention contains an acrylic monomer prepolymer that prevents powder sedimentation, an acrylic plasticizer that increases the flexibility of the gasket, a cross-linking agent that promotes the polymerization of the acrylic monomer, a phthalate coupling agent that improves the powder surface, and an organic peroxide thermal initiator and antioxidant required for gasket curing; the monomers selected above are acrylic soft monomers with low Tg values, and the acrylic monomer prepolymer is prepared by thermal polymerization and photopolymerization.

[0021] The thermally conductive filler portion is composed of one or more of alumina, boron nitride, aluminum nitride, and silicon carbide. The thermal conductivity of the acrylic thermal gasket can be adjusted by changing the shape, particle size, and type of the thermally conductive filler. The colloid and the thermally conductive filler portion are mixed by vacuum stirring, rolled on a calender, and solidified into shape. The acrylic thermal gasket prepared by this method has controllable thickness, excellent thermal conductivity, and good mechanical strength and insulation properties. Since the monomers used for the prepolymer and plasticizer of the colloid portion are all low-Tg acrylic soft monomers, and the formula does not involve substances that are easily volatile at high temperatures, the gasket has excellent high-temperature resistance and can be used to prepare high-performance thermal gaskets with high thermal conductivity and low hardness. DETAILED DESCRIPTION

[0022] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more precise definition of the protection scope of the present invention.

[0023] The present application provides a high-temperature resistant thermally conductive acrylic gasket. On the one hand, a low-Tg acrylic monomer prepolymer is used to solve the problems of acrylic gasket molding and high-temperature resistance. On the other hand, a non-functional acrylic polymer is used as a plasticizer to solve the mechanical properties of the acrylic thermally conductive gasket; a high thermal conductivity filler is used to prepare an acrylic thermally conductive gasket with a high thermal conductivity coefficient.

[0024] The acrylic polymer and acrylic polymer plasticizer involved in the present invention are both polymerized from acrylic monomers and serve as components of the colloid part. The polymerization method adopts thermal polymerization and photopolymerization to control the molecular weight.

[0025] Acrylic monomer:

[0026] The monomers used in the acrylic thermally conductive gasket of the present invention are not limited to a single monomer; one or more monomers can be mixed and used. The selected acrylic monomers all have a glass transition temperature below 0°C. Specific examples include ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, and hexyl methacrylate. Although the low Tg values ​​of these monomers significantly increase the material's flexibility, using them alone does not provide strong cohesion in the colloid. Therefore, acrylic monomers with a glass transition temperature greater than 20°C should also be used in combination. These acrylic monomers primarily include methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, n-(iso)butyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, glycidyl methacrylate, cyclohexyl methacrylate, and isobornyl methacrylate. Mixing these acrylic monomers can increase the crosslinking strength of the colloid, but excessive use should be avoided, as this can affect weather resistance. The preferred addition amount is 5% by weight of the soft acrylic monomer.

[0027] Initiators can undergo free radical polymerization and copolymerization reactions with monomers. Specifically, they are used in the preparation of acrylic monomer prepolymers and acrylic polymer plasticizers. Common initiators include organic peroxides, inorganic peroxides, azo peroxides, and redox peroxides. Organic peroxide initiators selected for use in the present invention primarily include acyl peroxides, hydroperoxides, dialkyl peroxides, ester peroxides, ketone peroxides, and dicarbonate peroxides. The preferred amount of initiator added is 1-5% of the monomer mass.

[0028] Monomer prepolymer:

[0029] The acrylic monomer materials used above all suffer from a low molecular weight. Simply mixing several monomers and adding thermally conductive fillers will cause the fillers to settle, and the low viscosity of the thermally conductive paste will cause leveling during the calendering process, making molding extremely difficult. Therefore, the acrylic monomer mixture is pre-polymerized to increase the molecular weight of the colloid and improve the viscosity of the system. However, the molecular weight should not be too high, as this will affect the filling of the thermally conductive powder. Partial polymerization can be performed in a variety of ways, such as thermal polymerization, photopolymerization, and electron beam polymerization.

[0030] During the prepolymerization of the monomer mixture, a molecular weight regulator, i.e., a chain transfer agent, may be added to control the molecular weight of the prepolymer. Examples of such chain transfer agents include mercaptans, disulfides, and carbon tetrabromide, one or more of which may be used in combination. The molecular weight of the prepolymer is preferably controlled between 3,000 and 50,000. The preferred amount of prepolymer added is 5-15% of the total weight of the formulation.

[0031] The preparation of acrylic acid prepolymer in the present invention can be divided into two methods: thermal polymerization and photopolymerization:

[0032] The thermal polymerization method is as follows: 100g of isooctyl acrylate or a mixture of isooctyl acrylate and other monomers is added to the monomers, 0.05-0.5g of lauryl peroxide or other organic peroxide thermal initiator is then added to the mixture, followed by 0.01-0.05g of 1-octanethiol or other organic thiol chain transfer agent. The monomer or monomer mixture, to which the initiator and chain transfer agent have been added, is placed in a constant-temperature water bath at 80°C, equipped with a condensing reflux device to prevent implosion during the polymerization process. When the reaction is complete, the polymerized colloid is removed from the container, which is the prepolymer of the acrylic monomer or monomer mixture.

[0033] The photopolymerization method is as follows: take 100g of isooctyl acrylate or a mixture of isooctyl acrylate and other monomers, add 0.05-0.5g of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide or other organic peroxide photoinitiator to the above monomers, and then add 0.01-0.05g of 1-octanethiol or other organic thiol chain transfer agent to the mixed liquid. Add a UV light source with a wavelength of 300-400nm at the bottom or around the reactor, preferably with an intensity of 3mW / cm 2 The monomers are then fully exposed to ultraviolet light during stirring. After the reaction is complete, the prepolymer of acrylic monomer or mixed monomer is removed. This method is simpler and faster to prepare than thermal polymerization, but it is more demanding, prone to incomplete and insufficient reactions, and has strict requirements on the number of reactions. It is not suitable for large-scale reaction preparations, making mass production difficult. Therefore, for these reasons, thermal curing is the preferred method for colloidal polymerization in the present invention.

[0034] Thermally Conductive Fillers: Currently, most thermally conductive fillers used in thermally conductive gaskets are non-metallic ceramic materials. While Cu, Al, and Ag powders can also exhibit high thermal conductivity, the addition of these metals significantly reduces the mechanical properties of the gasket and negatively impacts its insulation properties. Application in electronic devices can easily lead to short circuits in electronic components. Common thermally conductive fillers on the market include alumina, aluminum nitride, boron nitride, and silicon carbide. Alumina, due to its low price and simple preparation method, is highly favored by the thermal management material community. Pure alumina can achieve a thermal conductivity of 30 W / (m·K). Common alumina forms are spherical and flake. Generally speaking, spherical alumina, due to its lower specific surface area and bulk density, can significantly increase the amount of thermally conductive filler required, facilitating the overlapping of thermal channels and thus improving thermal conductivity. Flake alumina, due to its unique surface structure, is not conducive to overlapping thermal channels and significantly reduces the amount of thermally conductive filler required. Aluminum nitride has high thermal conductivity, and its thermal conductivity can reach 320W / (m·K). However, due to its special chemical properties, aluminum nitride is very easy to hydrolyze when absorbing moisture to form aluminum hydroxide, which can easily cause the device to short-circuit, and the price of aluminum nitride is generally high, so aluminum nitride is generally used as a doped mixture in thermal conductive formulas. Similarly, the thermal conductivity of boron nitride is 120W / (m·K). Compared with aluminum nitride, boron nitride is chemically stable, but due to its large specific surface area, the filling amount is also a big problem, so boron nitride is generally mixed with thermal conductive fillers such as aluminum oxide. The thermal conductivity of silicon carbide is 100W / (m·K), and its powder color is generally dark, and it is difficult to color. It has strict requirements on the color of the gasket, and the filling of silicon carbide will cause the insulation performance of the gasket to deteriorate, so it is not suitable for application scenarios with high insulation requirements. In summary, the thermal conductive filler selected in the present invention is a single aluminum oxide or a mixture of aluminum oxide and a single or multiple thermal conductive fillers. The thermally conductive filler is preferably added in an amount of 80-95% by weight of the overall formulation.

[0035] To supplement the aforementioned thermally conductive powder, the colloid prepared in this invention can also be filled with ferrite-based soft magnetic materials, giving the gasket a certain degree of electromagnetic wave shielding and absorption. Specific soft magnetic materials include Fe-Si-Al and carbonyl iron. Furthermore, thermally conductive fillers can be mixed with soft magnetic materials to create a gasket that not only has thermal conductivity but also a certain degree of electromagnetic wave absorption.

[0036] Traditional plasticizers have compatibility issues, and the cross-linking strength with the acrylic monomer in the colloid system is insufficient, and precipitation will occur after long-term use. In addition, such plasticizers are generally not ideal in terms of high-temperature resistance. Adding them to the formula can easily cause the thermal gasket to gradually evaporate over time at high temperatures, resulting in the gasket becoming harder and the thermal conductivity properties becoming worse.

[0037] Compared to traditional plasticizers, the acrylic plasticizer prepared in this invention is formed by polymerizing acrylic monomers. These monomers typically have a lower glass transition temperature and contain no or minimal functional groups. Specifically, they include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, and isobutyl acrylate. Polymers of these monomers exhibit high flexibility and excellent high-temperature resistance. When added to colloids, they exhibit good compatibility with acrylic monomers and significantly reduce the thermal resistance of the system.

[0038] The preparation method of the acrylic plasticizer in the present invention is the same as that of acrylic oligomers. An appropriate amount of initiator is added to a low glass transition temperature monomer, with the amount of initiator added ranging from 0.1% to 1% by weight of the monomer. A chain transfer agent is added at a level of 0.01% to 0.1% by weight of the monomer to control the molecular weight of the polymer. The molecular weight of the acrylic polymer plasticizer is preferably between 500 and 5000. A molecular weight too low results in insufficient crosslinking strength with the system and poor handling properties. A high molecular weight reduces the powder loading and leads to excessive plasticization, increasing the thermal resistance of the gasket. The preferred addition ratio of the acrylic plasticizer is 10-30% by weight of the acrylic prepolymer.

[0039] The acrylic acid prepolymer prepared in the present invention will have some residual acrylic acid monomers that are not fully polymerized. If such residual monomers cannot be completely removed during the subsequent thermal curing process, the high-temperature resistance of the thermally conductive gasket will be greatly affected. Under long-term high-temperature conditions, the active free radicals of the acrylic acid monomers will undergo oxidation reactions, causing the gasket to turn yellow in the later stage. Adding an appropriate amount of antioxidant to the formula can effectively solve this problem. The antioxidant can prevent the free radicals of the unreacted monomers from undergoing oxidation reactions. Such antioxidants mainly include: Basf 1010, 1076, 225, etc., and the preferred amount of antioxidant added is 1-5% of the acrylic acid prepolymer.

[0040] Generally speaking, thermally conductive fillers and acrylic colloids are non-isotropic materials. When adding inorganic thermally conductive fillers to acrylic colloids, there is a certain interfacial interaction. This interfacial interaction limits the compatibility of the two substances and affects the filling amount of the thermally conductive filler. In order to increase the dispersion and addition amount of the thermally conductive filler in the colloid, an appropriate amount of coupling agent should also be added to the formula. The coupling agent contains two groups with completely different chemical properties. One of them is an inorganic-friendly group that can chemically react with the surface of the inorganic thermally conductive filler; the other is an organic-friendly group that can combine with the organic molecular materials or polymers in the colloid. Specifically, the role of the coupling agent is equivalent to an adhesive between the colloid and the thermally conductive filler, which can enable the thermally conductive filler to be integrated into the required organic colloid as much as possible.

[0041] The choice of coupling agent depends primarily on the properties of the thermally conductive filler. It's important to select one containing groups that react readily with the filler. Suitable coupling agents for inorganic thermally conductive fillers such as alumina and aluminum nitride primarily include siloxanes and phthalates. Considering the gasket's high-temperature resistance, a coupling agent that doesn't volatilize easily at high temperatures is generally chosen. The preferred coupling agent addition ratio is 0.5-3% of the filler mass.

[0042] Example 1: A heat-curing thermally conductive acrylic gasket, comprising the following steps:

[0043] Step 1: Weigh 100 g of isooctyl acrylate, 0.5 g of 1,6-hexanediol diacrylate, and 30 g of butyl acrylate, stir and deaerate in a planetary mixer, add 0.5 wt% of dibenzoyl peroxide and a certain amount of 1-octanethiol to the mixture, stir under nitrogen protection and heat to 85°C, observe the reaction rate, control the molecular weight of the polymer to about 3000, and cool to obtain colloid A.

[0044] Step 2: Weigh 85 wt% of thermally conductive powder and 15 wt% of colloid A and mix them evenly. The mixture is stirred under high-speed vacuum to obtain a mixed thermally conductive filler. The thermally conductive filler is composed of a mixture of spherical alumina with particle sizes of 1 μm, 5 μm, and 45 μm (mass ratio of 1 μm:5 μm:45 μm = 1:3:5). The alumina used here is unsurface-modified.

[0045] Step 3: Place the thermally conductive filler between 50µm and 75µm thick PET films, using a 1-3g release film coated with silicone oil on one side. Roll the thermally conductive filler mixture using a double-roll calender at a speed of 0.7m / min to obtain a sheet-like acrylic thermal pad precursor. This sheet is then placed in an oven for high-temperature curing, resulting in the acrylic thermal pad.

[0046] The above-mentioned high-temperature oven curing involves multiple temperature ranges to prevent implosion during curing, which can affect the product appearance. The experiments used three different curing temperatures: 80°C, 100°C, and 120°C.

[0047] Examples 2-5: Examples 2-5 primarily illustrate the effects of adding plasticizers, antioxidants, crosslinkers, and coupling agents to the formulation on the appearance and performance of thermally conductive gaskets. The experimental results show that while adding traditional plasticizers and silane coupling agents significantly improves the thermal conductivity and hardness of the thermally conductive gasket, it significantly impacts the gasket's tensile strength and aging performance. Adding a crosslinker improves the gasket's tensile strength, while adding an antioxidant effectively enhances its temperature resistance.

[0048] The above additives are added in the following manner: after the monomers are mixed and polymerized into a prepolymer, and before the thermal conductive powder is added, the additives are added to the prepolymer and deaerated and stirred. For example, powdered materials such as antioxidants and initiators need to be heated and incorporated.

[0049] Comparative Examples 1-3: Comparative Examples 1-3 investigated the effects of different plasticizers and coupling agents on gasket performance. The results indicate that using a monofunctional acrylic oligomer as a plasticizer can address the issues of precipitation and heat resistance associated with traditional plasticizers. Adding a titanium-based coupling agent significantly improves the gasket's thermal conductivity and high-temperature resistance. The specific experimental procedures were consistent with those in Example 1.

[0050] Table 1: Effects of adding different additives on gasket performance

[0051]

[0052] Aging test:

[0053] Taking Comparative Example 3 as an example, the aging test performed in the above experiment included the following steps: the prepared acrylic thermal pads were cut into 100*100 square pieces and placed in a high-temperature vacuum drying oven at 130°C. The hardness and thermal conductivity of the pads were tested before placement. The hardness and thermal conductivity were then tested after 125, 250, 500, and 1000 hours of placement, and the changes in hardness and thermal conductivity were observed to determine the aging resistance. The results are shown in Table 2 below.

[0054] Table 2: Changes in gasket hardness and thermal conductivity under high temperature aging

[0055] Aging time 0 125 250 500 1000 Shore 00 hardness 52 53 53 53 54 Thermal conductivity 2.7 2.7 2.6 2.7 2.6

[0056] The test results show that the hardness and thermal conductivity of the thermal gasket did not change significantly after prolonged exposure to a high temperature of 130°C, indicating that the gasket has excellent high-temperature resistance.

[0057] Examples 6-9:

[0058] We investigated the effects of different powder ratios on the thermal conductivity and hardness of thermally conductive gaskets. The colloid was prepared using the method described in Example 1, with the addition of the thermally conductive filler and the preparation of the thermally conductive gasket also performed as described in the previous example. The experimental results are shown in Table 3 below: Increasing the proportion of the thermally conductive filler increased the thermal conductivity and slightly increased the hardness; decreasing the proportion of the thermally conductive filler decreased the thermal conductivity and decreased the hardness.

[0059] Comparative Examples 1-3:

[0060] To further enhance the thermal conductivity of thermally conductive gaskets, the present invention adds alumina as a thermally conductive filler to the aforementioned experiments. Furthermore, thermally conductive powders with higher thermal conductivity are added to enhance the gasket's thermal conductivity. Specific examples of thermally conductive powders with higher thermal conductivity include silicon carbide (SiC), boron nitride (BN), and aluminum nitride (AlN).

[0061] The specific addition method is as follows: the colloid used is prepared according to the preparation method in Example 1, and the prepared colloid is mixed with various additives such as plasticizers, crosslinking agents, and initiators to form the non-thermal conductive filler part. Alumina of various particle sizes are mixed together in a certain proportion (the ratio of different particle sizes of alumina in the following examples and comparative examples is: 1 micron: 5 microns: 45 microns = 1:3:6), and this part constitutes the thermal conductive filler part A. The thermal conductive filler part A and the non-thermal conductive filler part are first vacuum stirred and mixed to obtain a thermal conductive slurry. Various thermal conductive fillers with high thermal conductivity coefficients are added to the thermal conductive filler part A at a ratio of 1:10 parts, and then vacuum stirred to obtain the final thermal conductive slurry to be rolled. The mixed slurry is placed between PET coated with silicone oil on both sides, and calendered into the required sheet gasket through a calender. The calendered gasket is placed in a vacuum drying oven at 100°C for heat curing. After 20 minutes, the gasket is taken out and the release film is torn off to obtain the acrylic thermal conductive gasket.

[0062] The results are shown in Table 3 below: Adding a high thermal conductivity thermal conductive material can improve the thermal conductivity of the gasket to a certain extent, but each material has its negative effects. The addition of SiC significantly improves the thermal conductivity of the gasket, but the relative hardness will increase, and the volume resistivity of the gasket is 1.8*10^9 at this time, which has a certain conductivity risk. Due to the special property of AlN that it is easily hydrolyzed at high temperatures, the addition of AlN reduces the aging resistance of the gasket, and it is necessary to use a powder that is surface-treated and hydrolysis-resistant. Due to the large specific surface area of ​​BN, the viscosity of the system will be greatly increased. Adding a small amount of BN will solidify during the stirring process and cannot form a sheet.

[0063] Table 3: Effect of adding different thermal conductive fillers on gasket performance

[0064]

[0065] The experimental results of Examples 6-10 and Comparative Examples 4-6 show that increasing the powder ratio or adding high thermal conductivity materials can effectively improve the thermal conductivity of the gasket, but the hardness of the gasket is greatly affected. If you want to obtain a thermally conductive gasket with lower hardness, although reducing the powder ratio can be achieved, the thermal conductivity of the gasket will not meet the ideal requirements. Under the same material conditions, these two properties seem to be contradictory, so how to prepare a thermally conductive gasket with high thermal conductivity and low hardness becomes a difficult problem. Some people have proposed that when using DOP as a plasticizer, since the molecular weight of such plasticizers is relatively small, increasing the content of the plasticizer can effectively reduce the hardness of the gasket. However, this method cannot make the prepared thermally conductive gasket have long-term high temperature resistance. The small molecules in the plasticizer gradually precipitate under long-term high temperature conditions. After precipitation, the hardness of the gasket will also increase, thereby affecting the thermal conductivity. Moreover, if an excessive amount of low molecular weight plasticizer is added, the cross-linking strength inside the colloid is reduced, and thus the thermal conductive filler cannot be effectively wrapped, resulting in the mechanical properties of the gasket becoming very poor. In addition, under the premise of reasonable combination of thermal conductive fillers of various particle sizes, the thermal conductivity of thermal conductive particles with large particle size will be better than that of particles with small particle size. This is because thermal conductive fillers with large particle size are easier to build thermal conductive channels in the colloid.

[0066] Examples 10-14:

[0067] In the present invention, an acrylic polymer with higher molecular weight and better heat resistance is used as a plasticizer. Examples 10-14 study the effect of the addition amount of acrylic polymer plasticizer on the hardness and high temperature resistance of the gasket.

[0068] Comparative Examples 7-9:

[0069] In Comparative Examples 7-9, at the same ratio of thermally conductive filler to colloid, larger particle size powders were used to replace smaller particle size powders. Specifically, 70 μm, 90 μm, and 120 μm particle size thermally conductive powders were used to replace the 45 μm thermally conductive filler in the original formula. Specific experimental data are shown in Table 4 below:

[0070] Table 4: Effects of plasticizer addition and thermal conductive powder particle size on gasket performance

[0071]

[0072] Comparison of the results of Examples 11-12 with those of Example 8 shows that increasing the content of acrylic polymer plasticizer can reduce the hardness of the gasket and slightly improve the thermal conductivity; on the contrary, reducing the content of acrylic polymer plasticizer will increase the hardness of the gasket and reduce the thermal conductivity. Examples 13-14 show that increasing the ratio of plasticizer to acrylic prepolymer will reduce the hardness of the gasket and increase the thermal conductivity. However, too high a plasticizer content will reduce the mechanical strength of the gasket and increase the curing time. Comparative Examples 7-9 show that increasing the maximum size of the thermally conductive particles can effectively improve the thermal conductivity of the gasket, and the hardness of the gasket will not change. The above two methods of changing the hardness of the gasket will not affect the temperature resistance of the gasket.

[0073] The above embodiments merely illustrate the implementation methods of the present invention. Although the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that a person skilled in the art may make various modifications and improvements without departing from the scope of the present invention, and these modifications and improvements fall within the scope of protection of the present invention.

Claims

1. A high temperature resistant ultra-soft acrylic thermal pad, characterized by: The thermally conductive gasket comprises a colloid and a thermally conductive filler. The colloid is composed of a mixture of one or more acrylic monomers with a low glass transition temperature and acrylic monomer prepolymers, and further contains a photoinitiator or thermal initiator capable of initiating polymerization of the monomers. The colloid accounts for 5 to 15% of the total weight of the thermally conductive gasket. The heat-conducting filler is composed of one or more of aluminum oxide, boron nitride, aluminum nitride, and silicon carbide, and the heat-conducting filler accounts for 85-95% of the total weight of the heat-conducting gasket.

2. The high temperature resistant ultra-soft acrylic thermally conductive pad according to claim 1, characterized in that: The acrylic monomer is an acrylic monomer having a Tg value not greater than 0 and a carbon number not exceeding 20; the acrylic monomer also includes an acrylic monomer having a Tg value greater than 20 and an alkyl number not exceeding 20.

3. The high temperature resistant ultra-soft acrylic thermally conductive pad according to claim 1, characterized in that: The acrylic monomer prepolymer contained in the colloid is specifically any one or more of ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, and hexyl methacrylate, and its molecular weight is between 500-20,000.

4. The high temperature resistant ultra-soft acrylic thermally conductive pad according to claim 1, characterized in that: The thermal initiator or photoinitiator is an organic peroxide; Organic peroxides include: one or more combinations of acyl peroxides, hydroperoxides, dialkyl peroxides, ester peroxides, ketone peroxides, and dicarbonate peroxides. The amount of the thermal initiator or photoinitiator added should be 1-5% of the mass of the acrylic monomer.

5. The high temperature resistant ultra-soft acrylic thermally conductive pad according to claim 4, characterized in that: The acyl peroxide is benzoyl peroxide or lauroyl peroxide; the hydroperoxide is cumene hydroperoxide or tert-butyl hydroperoxide; the dialkyl peroxide is di-tert-butyl peroxide or dicumyl peroxide; the ester peroxide is tert-butyl perbenzoate or tert-butyl pervalerate; the ketone peroxide is methyl ethyl ketone peroxide or cyclohexanone peroxide; and the dicarbonate peroxide is diisopropyl peroxydicarbonate or dicyclohexyl peroxydicarbonate.

6. The high temperature resistant ultra-soft acrylic thermally conductive gasket according to claim 1, characterized in that: The colloid also includes acrylic plasticizer, antioxidant, cross-linking agent, flame retardant, coupling agent; The acrylic plasticizer is a polymer formed by polymerization of acrylic acid monomers, specifically including any one or more combinations of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, and isobutyl acrylate, and the molecular weight of the plasticizer is controlled at 500-5000; The antioxidant is a hindered phenol, including any one or more combinations of 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate) ester, and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; The coupling agent is a phthalate coupling agent, including any one or more combinations of monoalkoxy type, pyrophosphate type, chelate type and coordination type.

7. A method for preparing the high-temperature resistant ultra-soft acrylic thermally conductive gasket according to claim 1, characterized in that: The specific preparation steps are as follows: the colloid and the thermal conductive filler are mixed, stirred and degassed to obtain a thermal conductive slurry, the two sides of the thermal conductive slurry are placed between PET release films, pressed into sheets by a calender, and then baked and cured at high temperature. After the curing is completed, an acrylic thermal conductive gasket is obtained.

8. The method for preparing the high temperature resistant ultra-soft acrylic thermally conductive gasket according to claim 7, characterized in that: The acrylic thermal conductive gasket has a thickness of 0.2mm-10mm, a thermal conductivity of 1.5-8W, and a hardness of ASKC 5-50. A substrate is added during the calendering process to obtain an acrylic thermal conductive gasket containing a substrate, or a release film on one side is replaced with a PET film to obtain an acrylic thermal conductive gasket with a non-sticky side.

Citation Information

Patent Citations

  • Acrylic thermally conductive composition, and thermally conductive sheet

    CN106459237A

  • Thermocuring heat-conducting acrylate gasket and preparation method thereof

    CN117384603A

  • Acrylic-based thermally conductive composition, sheet, and process

    WO2003093336A1

  • Acrylic thermally conductive composition, and thermally conductive sheet

    WO2015178332A1